2018
DOI: 10.3389/fonc.2018.00332
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of Circular RNA in Hepatocellular Carcinoma: A Novel Potential Biomarker and Therapeutic Target

Abstract: CircRNA, a kind of tissue specific and covalently closed circular non-coding RNA is very abundant in eukaryocyte. Generally, circRNA is generated by back-splicing of protein-coding genes' pre-mRNA. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world. Due to the characteristics of poor prognosis and high recurrence, the pathogenesis of HCC is highly concerned by researchers worldwide. Recent studies demonstrated that numerous circRNAs were differentially expressed in HCC tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 143 publications
(190 reference statements)
0
57
0
Order By: Relevance
“…Compared with linear RNA, circRNAs are more stable, abundant, conserved due to its special circular structure. 4 , 5 Recently, studies have demonstrated that a novel circRNA, circMAT2B, can contribute to cell proliferation, thereby promoting the growth of hepatocellular carcinoma (HCC). 6 However, the precise mechanisms of circMAT2B-induced CRC cell proliferation are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with linear RNA, circRNAs are more stable, abundant, conserved due to its special circular structure. 4 , 5 Recently, studies have demonstrated that a novel circRNA, circMAT2B, can contribute to cell proliferation, thereby promoting the growth of hepatocellular carcinoma (HCC). 6 However, the precise mechanisms of circMAT2B-induced CRC cell proliferation are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21 What is important, circRNAs are also potential molecules, functioning in the diagnosis, therapy, and prognosis of patients with HCC. 22 It is a fact that numerous circRNAs often exhibit cell type-specific, tissue-specific or developmental stage-specific expression. 23 , 24 Situated at chromosome X: 139865339-139866824, circ_CDR1as (also named as hsa_circ_0001946 or ciRS-7), is a risk factor for HCC; Besides, circ_CDR1as is downregulated in HCC cells and tissues, affecting physiological function of HCC cells by targeting miR-7 and regulating EGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…137 Overall, circRNAs played key roles in tumorigenesis and development, epigenetic regulation, drug resistance, and could be considered as immune-associated biomarker and therapeutic target in HCC. [138][139][140][141][142][143][144] Regardless, more in-depth study of circRNA biofunctions in HCC is greatly desired.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%